2011
DOI: 10.1890/10-1542.1
|View full text |Cite
|
Sign up to set email alerts
|

Different farming and water regimes in Italian rice fields affect arbuscular mycorrhizal fungal soil communities

Abstract: Arbuscular mycorrhizal fungi (AMF) comprise one of the main components of soil microbiota in most agroecosystems. These obligate mutualistic symbionts colonize the roots of most plants, including crop plants. Many papers have indicated that different crop management practices could affect AMF communities and their root colonization. However, there is little knowledge available on the influence of conventional and low-input agriculture on root colonization and AMF molecular diversity in rice fields. Two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 58 publications
3
53
2
Order By: Relevance
“…The presence of AMF in wetland ecosystems has received increased attention in recent years (7,9,32,33), but only a few field studies documenting AMF colonization have been conducted in paddy wetlands (2). In agreement with Watanarojanaporn et al (13), who reported that AMF are commonly present in rice roots from conventional paddy wetlands in Thailand, we found that AMF colonization in rice roots is commonly present at the heading and ripening stages though absent or rare at the early growth stages.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The presence of AMF in wetland ecosystems has received increased attention in recent years (7,9,32,33), but only a few field studies documenting AMF colonization have been conducted in paddy wetlands (2). In agreement with Watanarojanaporn et al (13), who reported that AMF are commonly present in rice roots from conventional paddy wetlands in Thailand, we found that AMF colonization in rice roots is commonly present at the heading and ripening stages though absent or rare at the early growth stages.…”
Section: Discussionsupporting
confidence: 89%
“…The AMF communities of some wetland habitats have been investigated (7,8,9,10,11), but whether AMF occur in paddy rice fields under waterlogged conditions is still under debate (12). Some studies found that AMF are able to survive in waterlogged paddy wetlands (13), but there are also reports showing that AMF are absent or rare due to the anoxic conditions that often prevail in waterlogged systems (2,14).AMF communities are not static within an ecosystem as the fungi are affected by changing biotic and abiotic factors (3). In order to gain insights into the functional role of AMF, it is important to obtain more knowledge on their distribution dynamics in different ecosystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Acaulospora, generally is not frequent in the arable lands [20,26], because not disturbance tolerant. In our work it appeared o be well represented, also in a par- ticular condition like rice grown in flooding regime, where members of the family Glomeraceae (Funneliformis, Rhizophagus ...) were expected [22]. The uncultured Acaulospora sequence phylogenetically related to RP2 was obtained in an unpublished study on rice cultivation in Thailand.…”
Section: Resultsmentioning
confidence: 53%
“…These data could find an explanation in the flooding regime the crop was subjected to. As reported in several publications flooding has a negative impact both on root colonization and spore abundance in the soil, probably to the anoxic environment [21,22]. Other studies showed that AMF can colonize roots of aquatic plants depending on the affiliation to monocots or dicots species [23].…”
Section: Resultsmentioning
confidence: 84%